Identifying At-Risk College Student Drinkers With the AUDIT-US: A Receiver Operating Characteristic Curve Analysis. (September 2020) - Madson, Michael B.; Schutts, Joshua W.; Jordan, Hallie R.; Villarosa-Hurlocker, Margo C.; Whitley, Robert B.; Mohn, Richard S.
The Alcohol Use Disorders Identification Test (AUDIT) is the gold standard screening measure. Recently, there has been increasing call to update the measure to reflect harmful drinking standards in the United States. The purpose of this study was to use receiver operating characteristic curve analysis to evaluate the AUDIT and the United States version (AUDIT-US). Participants were 382 traditional age ( M = 20.2, SD = 1.5) college students (68.7% female, 64.9% White) who had consumed alcohol at least once in the 30 days prior to participating. Although results provide evidence for the AUDIT and the AUDIT-US as valid screening tools, the Consumption subscale of the AUDIT-US performed the best in predicting at-risk college drinkers. The Consumption subscale of the AUDIT-US with a single cutoff score of four appears to be the optimal and most parsimonious method of identifying at-risk college drinkers.